Violence and space: An introduction to the geographies of violence. (May 2016) - Springer, Simon; Le Billon, Philippe
Abstract: Violence is a confounding concept. It frequently defies explanation and lacks an agreed upon definition. Yet geographers are well positioned to bring greater conceptual clarity to violence by thinking through its intersections with space. In setting the tone for this special issue on Violence and Space we highlight some of the key lines of flight that have shaped geographical thinking on violence. While there are a significant number of geographers interested in the question of violence, the field of 'geographies of violence' remains an emerging area of research that deserves greater attention and a more rigorous examination. By emphasizing the spatiality of violence, this special issue aims to contribute to a more sustained conversation on the violent geographies that shape our daily lives, our encounters with institutions, and the various structures that configure our social organization. This introduction is but an initial sketch of what we believe needs to be a much larger and unfolding research agenda dedicated to understanding violence from a geographical perspective.